Memahami Faktor Psikologis dan Fisiologis dalam Mendesain UI yang Ramah Pengguna - Zulia Lestari Nasution; Alfin Gimnastiar; Muhammad Wahyu Ramadhan; Rizky Abdillah (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Designing a user interface (UI) requires a deep understanding of how users think and interact with systems. This study explores the psychological and physiological aspects that influence user interaction with UI, such as perception, cognitive load, reaction time, and ergonomic factors. Through literature analysis and UI usability testing, this paper identifies design principles that enhance user experience by aligning interface structures with human capabilities. The results show that interfaces built with attention to psychological factors like user memory and attention span, as well as physiological aspects such as eye movement and hand positioning, significantly improve user satisfaction and efficiency.